Neural stem cell transplantation in ischemic stroke: A role for preconditioning and cellular engineering. Issue 7 (July 2017) - Bernstock, Joshua D; Peruzzotti-Jametti, Luca; Ye, Daniel; Gessler, Florian A; Maric, Dragan; Vicario, Nunzio; Lee, Yang-Ja; Pluchino, Stefano; Hallenbeck, John M
Ischemic stroke continues to be a leading cause of morbidity and mortality throughout the world. To protect and/or repair the ischemic brain, a multitiered approach may be centered on neural stem cell (NSC) transplantation. Transplanted NSCs exert beneficial effects not only via structural replacement, but also via immunomodulatory and/or neurotrophic actions. Unfortunately, the clinical translation of such promising therapies remains elusive, in part due to their limited persistence/survivability within the hostile ischemic microenvironment. Herein, we discuss current approaches for the development of NSCs more amenable to survival within the ischemic brain as a tool for future cellular therapies in stroke.